Quantitative assessment of telomerase components in cancer cell lines. Issue 9 (5th March 2015) - Akıncılar, Semih Can; Low, Kee Chung; Liu, Chia Yi; Yan, Ting Dong; Oji, Asami; Ikawa, Masahito; Li, Shang; Tergaonkar, Vinay
Abstract : Besides its canonical function of catalyzing the formation of telomeric repeats, many groups have recently reported non‐canonical functions of hTERT in particular, and telomerase in general. Regulating transcription is the central basis of non‐canonical functions of telomerase. However, unlike reverse transcriptase activity of telomerase that requires only a few molecules of enzymatically active hTERT, non‐canonical functions of hTERT or other telomerase components theoretically require several hundred copies. Here, we provide the first direct quantification of all the telomerase components in human cancer cell lines. We demonstrate that telomerase components do not exist in a 1:1 stoichiometric ratio, and there are several hundred copies of hTERT in cells. This provides the molecular basis of hTERT to function in other signaling cascades, including transcription. Abstract : Quantification of telomerase components in human cancer cell lines. Telomerase components do not exist in 1:1 stoichiometric ratio. hTERT molecules in cancer cell lines are about 665, suggesting that there are sufficient hTERT molecules to function in extra‐telomeric pathways. The number of telomerase components in the cell varies dramatically; hence they may have other functions in the cell.